Adaptação transcultural do instrumento “Quantum Caring Practice Self-assessment” para o português do Brasil - Hausen, Camila Freitas (2023)
Introduction: Despite advances in neonatal care, which have enabled increased survival of premature newborns, there are still challenges related to complications arising from immaturity. Among these, short- and long-term complications, caused by stress, handling and hyperstimulation to which these newborns are submitted during their stay in the Neonatal Intensive Care Unit (NICU), stand out. From this perspective, there is Developmental Care, which is a set of strategies that are anchored in protecting the overall development of the newborn and in neuroprotection. For the evaluation and monitoring of Developmental Care, there is an American instrument called Quantum Caring Practice Self-assessment, which has 75 items, divided into five central measures (Therapeutic environment; Prevention, assessment and management of pain and stress; Protected sleep; Activities of Daily Living and Family Collaborative Care), which aims to assess the frequency of practice of developmental care for premature infants admitted to the NICU. Objective: To perform cross-cultural adaptation to the Brazilian Portuguese language of the “Quantum Caring Practice Self-assessment”. Methods: Methodological study, of cross-cultural adaptation, followed the stages of translation, synthesis of translations, back-translation, expert committee and pre-tests. The pretest scenario (test and retest) was an Intensive Care Unit in the interior of Rio Grande do Sul, with the participation of 67 professionals from the multidisciplinary team. Data were collected in person using digital tools. The analysis of the level of equivalence and clarity was performed using the level of agreement, as well as simple descriptive analysis with relative frequency. The reliability of the instrument was based on the Inter-Class Interval. (ICC). The analysis of the data resulting from the application of the instrument was descriptive. Results: The stages of the cross-cultural adaptation process were strictly followed, thus achieving semantic, idiomatic, cultural and conceptual equivalence. The adjustments made were mostly related to cultural issues. An equivalence index, from the expert committee stage, of 95,4% of agreement was obtained, and a clarity index, resulting from the clarity test, of 94,5% of agreement, in the second round. The instrument translated and culturally adapted to Brazil reached an ICC of 0,62, suggesting the instrument's stability, recognizing sample limitations. As for the evaluation of Developmental Care, in the context where the pre-test was applied, the respective NICU performs the practices frequently (Md=4), being within the recommended range. Conclusion: Equivalences were reached between the original and translated version of the instrument, as well as the results regarding the stability of the instrument translated and adapted into Portuguese (BR), indicating its use for the evaluation of developmental care in the NICU, as well as to guide practices and Permanent Education in services.